2017
DOI: 10.21037/sci.2017.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant RNA splicing and mutations in spliceosome complex in acute myeloid leukemia

Abstract: The spliceosome, the cellular splicing machinery, regulates RNA splicing of messenger RNA precursors (pre-mRNAs) into maturation of protein coding RNAs. Recurrent mutations and copy number changes in genes encoding spliceosomal proteins and splicing regulatory factors have tumor promoting or suppressive functions in hematological malignancies, as well as some other cancers. Leukemia stem cell (LSC) populations, although rare, are essential contributors of treatment failure and relapse. Recent researches have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 100 publications
1
29
0
Order By: Relevance
“…Recent evidence has shown that aberrant splicing due to multiple mutations in the splicing pathway genes in myelodysplastic syndromes and AML constitutes an important pathophysiologic mechanism. [57][58][59][60] In the current study, the role of CDK9 in splicing was not fully evaluated, but future studies should address this. This would be particularly relevant, because CDK9 inhibition in both MDS and AML could potentially provide a unique therapeutic strategy to target aberrant splicing.…”
Section: Discussionmentioning
confidence: 92%
“…Recent evidence has shown that aberrant splicing due to multiple mutations in the splicing pathway genes in myelodysplastic syndromes and AML constitutes an important pathophysiologic mechanism. [57][58][59][60] In the current study, the role of CDK9 in splicing was not fully evaluated, but future studies should address this. This would be particularly relevant, because CDK9 inhibition in both MDS and AML could potentially provide a unique therapeutic strategy to target aberrant splicing.…”
Section: Discussionmentioning
confidence: 92%
“…The unlimited proliferation and evasion of apoptosis as well as differentiation arrested are characteristic of AML cells [ 33 , 34 ]. Deregulated signal transduction pathways, resulting from multiple genetic or epigenetic lesions, are believed to be the fundamental causes of the leukemogenesis [ 35 37 ]. Elevated expression of PRL-3 has been identified in about half of AML bone marrow samples and associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…More than 10 years ago, cancer stem cell (CSC) has been described as the origin of various cancers and is associated to disease progression [ 53 ]. These CSC populations are rare, and are functionally and phenotypically different form the bulk of tumor cells.…”
Section: Introductionmentioning
confidence: 99%